Prevalence of tick-borne bacterial pathogens in Germany—has the situation changed after a decade? - Mertens-Scholz, Katja; Hoffmann, Bernd; Gethmann, Jörn M.; Brangsch, Hanka; Pletz, Mathias W.; Klaus, Christine (Frontiers in Cellular and Infection Microbiology, 2024)
Tick-borne pathogens, such as Borreliella spp., Rickettsia spp. and Anaplasma spp. are frequently detected in Germany. They circulate between animals and tick vectors and can cause mild to severe diseases in humans. Knowledge about distribution and prevalence of these pathogens over time is important for risk assessment of human and animal health. Ixodes ricinus nymphs were collected at different locations in 2009/2010 and 2019 in Germany and analysed for tick-borne pathogens by realtime PCR and sequencing. Borreliella spp. was detected with a prevalence of 11.96% in 2009/2010 and 13.10% in 2019 with B. afzelii and B. garinii as dominant species. Borrelia miyamotoi was detected in seven ticks and in coinfection with B. afzelii or B. garinii. Rickettsia spp. showed a prevalence of 8.82% in 2009/2010 and 1.68% in 2019 with the exclusive detection of R. helvetica. The prevalence of Anaplasma spp. was 1.00% in 2009/2010 and 7.01% in 2019. A. phagocytophilum was detected in seven tick samples. None of the nymphs were positive for C. burnetii. Here observed changes in prevalence were not significant after a decade, but require longitudinal observations including parameters like host species and density, climatic factors to improve our understanding of tick-borne diseases.